2016
DOI: 10.15448/1980-6108.2016.3.22956
|View full text |Cite
|
Sign up to set email alerts
|

Adesão à dieta por idosos com síndrome metabólica assistidos na Estratégia Saúde da Família: frequência e associação com depressão

Abstract: Este artigo está licenciado sob forma de uma licença Creative Commons Atribuição 4.0 Internacional, que permite uso irrestrito, distribuição e reprodução em qualquer meio, desde que a publicação original seja corretamente citada. EMI-SUS).A avaliação da adesão à dieta foi realizada através de um questionário, elaborado pelos pesquisadores com base nas recomendações da I Diretriz Brasileira de Síndrome Metabólica, sobre a adesão a oito possíveis orientações dietéticas recebidas de profissionais da saúde (em re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
2
0
2
Order By: Relevance
“…Given the worsening of the patient's anthropometry, his food plan might have not been good, a result similar to a study conducted with elderly patients with metabolic syndrome, in which only a third of the studied population presented adherence to the diet 15 , which reinforces that the adoption of a healthy eating plan is essential in the treatment of SM, which aims to improve insulin sensitivity and prevent cardiovascular and metabolic changes associated with it.…”
Section: Discussionsupporting
confidence: 66%
“…Given the worsening of the patient's anthropometry, his food plan might have not been good, a result similar to a study conducted with elderly patients with metabolic syndrome, in which only a third of the studied population presented adherence to the diet 15 , which reinforces that the adoption of a healthy eating plan is essential in the treatment of SM, which aims to improve insulin sensitivity and prevent cardiovascular and metabolic changes associated with it.…”
Section: Discussionsupporting
confidence: 66%
“…A study in Porto Alegre described the frequency of adherence to diet and analyzed its association with depression in the elderly population with metabolic syndrome and found that 72 participants (66.1%) were classified as non-adherent and 37 (33.9%) were considered adherent. In the depressed elderly participants, adherence to the guidelines to avoid the consumption of sweets and sugar was lower (JACONDINO et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Por sua vez, a correlação positiva entre o estado nutricional e sintomas depressivos constitui indicativo da necessidade de estes aspectos serem considerados no planejamento da assistência, uma vez que indivíduos que possuem DM2 e depressão, concomitantemente, podem apresentar maior dificuldade na implementação de mudanças na alimentação, em decorrência de reduzida motivação (18) . Estudo de coorte realizado com 1.201 indivíduos com DM2 ao longo de cinco anos, apontou que a prevalência de depressão foi persistente durante todo o período nos indivíduos com IMC mais elevado, fato este que reitera a necessidade de intervenções precoces e intensivas em indivíduos com essa sobreposição de diagnósticos (19) .…”
Section: Resultsunclassified